Rcor2 Is Required for Somatic Differentiation and Represses Germline Cell Fate - Lijuan Pei; Hongjie Zhang; Meihui Zhang; Yixuan Wang; Ke Wei (Stem Cells International)
Rcor2, the corepressor 2 of REST, a transcriptional repressor, is predominantly expressed in embryonic stem cells (ESCs) and plays a major role in regulating ESC pluripotency and neurogenesis. The function of Rcor2 in development of other germ layers is yet unclear. We utilized a Rcor2-/- mouse embryonic stem cell (mESC) line to investigate the role of Rcor2 in mESC differentiation. Rcor2-/- mESC shows reduced proliferation and severely compromised capacity to differentiate to all three germ layers. In contrast, Rcor2 knockout promotes primordial germ cells (PGCs) specific gene expression and possibly PGC formation. Mechanistically, we revealed that Rcor2 inhibits expression of genes required for PGC development, such as Dppa3 and Dazl, by associating to their promoters and enhancing local suppressive H3K9me3 modifications. Our results suggest that Rcor2 plays an important role in somatic cell fate determination by suppressing PGC differentiation through regulating epigenetic modifications of PGC specific genes.